2015
DOI: 10.1093/jeg/lbv010
|View full text |Cite
|
Sign up to set email alerts
|

Regions and material flows: investigating the regional branching and industry relatedness of port traffics in a global perspective

Abstract: This article proposes a quantitative analysis of the interdependencies between port specialization and regional specialization across the world. A global database is elaborated, covering about 360 port regions located in both developed and developing countries. One main goal is to verify how interdependent port traffic and regional characteristics are, in a context of increasingly flexible commodity and value chains. Despite the aggregated dimension of available data and the heterogeneity of local situations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 83 publications
3
41
0
Order By: Relevance
“…Within this framework, it is important to stress that over 80% of international trade involves maritime services (Unctad, 2016), giving to port infrastructure a crucial role to improve international connectivity and propensity to international trade for a given region (e.g. Guerrero et al, 2016, Ducruet andNotteboom, 2012;Ducruet and Itoh, 2016). Moreover, as also underlined by Rodrigue et al (2016), transport systems are normally represented by networks in which nodal infrastructure (such as ports) plays a key role, by promoting accessibility and fostering local competitiveness for the hosting regions.…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, it is important to stress that over 80% of international trade involves maritime services (Unctad, 2016), giving to port infrastructure a crucial role to improve international connectivity and propensity to international trade for a given region (e.g. Guerrero et al, 2016, Ducruet andNotteboom, 2012;Ducruet and Itoh, 2016). Moreover, as also underlined by Rodrigue et al (2016), transport systems are normally represented by networks in which nodal infrastructure (such as ports) plays a key role, by promoting accessibility and fostering local competitiveness for the hosting regions.…”
Section: Introductionmentioning
confidence: 99%
“…Such evidence has been confirmed through a number of models and case studies about the physical and functional separation between ports and cities in the last decades (Bird, 1963;Hoyle, 1989;Murphey, 1989;Norcliffe et al, 1996). Other studies have demonstrated the temporal and geographic variability of such a phenomenon (Brocard, 1988;Ducruet and Lee, 2006;Lee et al, 2008;Ducruet and Itoh, 2016), echoing earlier critiques of the central place theory ignoring the port function, using the concept of gateway (Burghardt, 1970;Bird, 1973). In Europe, port cities were found to be demographically larger (Vleugels, 1969) and economically richer (Lever, 1995) than other cities.…”
Section: Introductionmentioning
confidence: 80%
“…696 & 713-716)). Moreover, Ducruet and Itoh (2016) find port throughput specialization largely reflects local economic specialization. A structural change in manufacturing production and trade pattern is thus expected.…”
Section: Omitted Variables and Additional Concernsmentioning
confidence: 98%